The relationship between work-life balance and employees’ well-being among non-academic employees at the chancellory building in Universiti Malaysia Sarawak (UNIMAS) Kota Samarahan, Sarawak / Christina Sayu Jelian - Jelian, Christina Sayu (2018)
The purpose of this study is to study the relationship between Work-Life Balance and Employees’ Well-Being at the Chancellory building in Universiti Malaysia Sarawak (UNIMAS). This study examines the relationship between work-family conflict and family-work conflict towards employees’ well-being at the Chancellory building of UNIMAS.To carry out this study, 87 questionnaires were distributed to employees at the Chancellory building of UNIMAS. All questionnaires were returned with 100% responding rates. The data were analyzed using Statistical Package Social Science (SPSS) version 25. The result of this study shows that, there is positive, significant and strong relationship between independent variables, Work-Family Conflict (.618**), Family-Work Conflict (.621**) and dependent variable,Employees’ Well-Being. It was found that employees of UNIMAS disagreed that WFC and FWC gave an impact towards their well-being. The researcher has recommended that UNIMAS should implement flexible work schedule for their employees. It is also recommended that the future researcher expands the sample size, compares the similar study between non-academic and academic employees, and conducts future research in government sectors.